Criação de laboratórios virtuais para a aquicultura - CIESLAK, Igor de Albuquerque (2019)
The present study presents the trajectory for the production of the Game Aquafish Simulator, the genre simulation, thought for the teaching of aquaculture, with the plot happening in the scenario of the Ifpa/Advanced Campus Vigia, in the homonymous municipality, in the state of Pará. The main objectives of this study are: a) that the teaching by means of virtual laboratories cause satisfaction, fun, enjoyable, captivating (motivating) and interesting; b) that the virtual laboratories are completely in agreement with the theory taught in room; c) that the student can better understand the themes presented in the virtual laboratories; d) that the student feels challenged in the activities proposed in the virtual laboratories and; e) that the game will be able to promote immersion. The methodology adopted has been outlined by reconciling the needs of the labor market (composed by farmers and public managers) and the academy (composed by students and teachers) in the definition of laboratories and aquatic species to be simulated. This population was consulted via closed questionnaires. It was also necessary to use focal group to fill in the Game Design Document (GDD) or also known as design documentation of digital games. For the conclusion of the game was necessary to produce 4.976 files distributed between images, sounds, sound effects, cutscenes and XML files, in addition to 8.327 lines of programming code. The game was developed for Multiplatforms, namely: computers with Windows 32-bits operating system, Windows 64-bits Linux 32-bits, 64-bits Linux, Android and iOs phones, tablets and websites in HTML5. The alpha version of the game was tested with students and teachers of Advanced Campus Vigia to get feedback. At the end of the work, users testers of the game almost unanimously confirmed that the game has proved to be quite successful in relation to the purposes suggested for the same and a win for the teaching of aquaculture and fisheries resources of the Advanced Campus Vigia